PERLAKUAN AKUNTANSI PRODUK AGRIKULTUR DAN TANAMAN PRODUKTIF BERDASARKAN PSAK 69 DAN PSAK 16 (Studi Kasus pada PT. Duta Putri Bersaudara) - Haniyah Putri W (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2019)
This study aims to present the accounting treatment of agricultural products and productive plants at PT. Duta Putri Bersaudara in accordance with PSAK 69 and PSAK 16 guidelines. PT. Duta Putri Brothers will conduct an IPO, while the company previously used SAK ETAP guidelines. In PSAK 69, it regulates the accounting treatment related to agricultural activities. In PSAK 16 regulating fixed assets, the amendments to PSAK 16 on agriculture adding productive plants related to agricultural activities are included in the scope of PSAK 16. This research method is a qualitative research with a case study approach. The case study approach is used because researchers focus on a particular case in depth in a company. Research data collection techniques, namely by interview, observation, and documentation. The results of this study indicate that PT. Duta Putri Bersaudara recognizes agricultural products (dates) as a supply of date plants in the current assets group, recognition of productive plants (date plants) in the non-current assets group, and there is no classification of date palms into Producing Plants and Immature Plants. PT. Duta Putri brothers also recognize the depreciation of productive plants as a depreciation expense. The measurement of agricultural products in PT. Duta Putri Bersaudara is measured based on fair value method, while the measurement of productive plants is based on the acquisition price which is accumulated from the costs of land preparation, planting seeds, and maintenance costs. The stage of disclosure of gains or losses arising is not recorded because PT. Duta Putri Brothers do not use the fair value method. From the accounting treatment stage, the company has not presented financial statement in accordances with PSAK 69 guidelines.Keywords: agricultural products, productive plants, PSAK 69